Fotoluminescência de SrTiO3 dopado com Al, Y, Cr, V e Nb - Soledade, Luiz Edmundo Bastos (Universidade Federal de São Carlos, 2003)
It was studied the effect of the dopants, Al, Y, Cr, Nb and V, on the photoluminescent properties of films and powders of amorphous strontium titanate. With this purpose the techniques of SEM, XRD, UV/Visible spectroscopy and room temperature photoluminescence were applied to film and powder samples of strontium titanate, prepared by the Pechini method. A literature survey was undertaken upon the structure and the photoluminescent properties of 26 crystalline inorganic titanates, in which titanium displayed the sixfold, fivefold and fourfold oxygen coordinations. The fivefold oxygen coordinated compounds exhibited much higher values of excitation band energy and quenching temperature than the sixfold oxygen coordinated compounds. A recent research from LIEC confirmed, by means of XANES, the presence of fivefold oxygen coordinated titanium in the samples of amorphous titanates that presented room temperature photoluminescence. A recent quantum mechanic study of LIEC associated the titanate amorphous structure to the reduction of its theoretical gap and therefore to the increase photoluminescence intensity. In the present work, were confirmed higher values of optical bandgaps for the crystalline samples than for the amorphous samples, supporting the creation of intermediate states in the forbidden band, which were recently confirmed in the aforementioned quantum mechanic study. It can be definitively stated that amorphous strontium titanato is sensitive to the doping. Generally speaking the chromium doping presents the tendency to decrease of the wavelength of the photoluminescence emission peak, while the opposite was observed in the case of the vanadium doping. The separation of the photoluminescence spectra could be very effectively accomplished into just two gaussians. For the case of the powder and tablet samples, the peak of smaller wavelength, µ1, is located within a narrow range from 561 to 571 nm. The peak of higher wavelength, µ2, is also located within a narrow range, in this case between 637 and 651 nm. These peak values reasonably agree with the values found for samples of amorphous undoped ZT, also in the form of powders. It should not be attributed to the dopants the responsibility for the photoluminescence phenomenon of the amorphous titanates. They only create defects that can influence, positively or negatively, the photoluminescence intensity, not having contributed to the creation of a new photoluminescence center. It can be said that the doping of amorphous strontium titanate only secondarily influences the previously important photoluminescence of the amorphous undoped SrTiO3 , which presents a quenching temperature over 300K. Similar results, of such secondary importance of the doping of amorphous titanates were observed in recent works of LIEC in Er-doped lead titanate, amorphous and crystalline, and in amorphous BaTiO3/SrTiO3 doped with Cr and V.
Keywords: Transformação de energia; Fotoluminescência; Titanato de estrôncio; Dopagem; CIENCIAS EXATAS E DA TERRA::QUIMICA